Assembly of Viral Hydrogels for Three‐Dimensional Conducting Nanocomposites. (30th April 2014) - Chen, Po‐Yen; Hyder, Md Nasim; Mackanic, David; Courchesne, Noémie‐Manuelle Dorval; Qi, Jifa; Klug, Matthew T.; Belcher, Angela M.; Hammond, Paula T.
<x xml:space="preserve">Abstract</x> M13 bacteriophages act as versatile scaffolds capable of organizing single‐walled carbon nanotubes and fabricating three‐dimensional conducting nanocomposites. The morphological, electrical, and electrochemical properties of the nanocomposites are presented, as well as its ability to disperse and utilize single‐walled carbon nanotubes effectively. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>